Pathophysiology and emerging biomarkers of cardiovascular-renal-hepato-metabolic syndrome - Nzobokela, John; Muchaili, Lweendo; Mwambungu, Alick; Masenga, Sepiso K.; Kirabo, Annet (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular-Renal-Hepatic-Metabolic (CRHM) syndrome characterizes a complex, interrelated disease framework that encompasses cardiovascular disease, chronic kidney disease (CKD), metabolic dysfunction-associated steatotic liver disease, and metabolic disorders such as obesity, type 2 diabetes mellitus, dyslipidemia, and hypertension. The syndrome extends the concept of cardiovascular-Kidney-Metabolic syndrome by incorporating the liver's pivotal role in systemic metabolic dysfunction. This syndrome progresses through a cycle of chronic inflammation, insulin resistance, oxidative stress, and endothelial dysfunction, driving multi-organ failure and increasing morbidity and mortality. Understanding the mechanistic keystones of this syndrome is critical for refining risk stratification and therapeutic interventions. Traditional inflammatory markers, such as C-reactive protein, interleukin-6, and tumor necrosis factor-alpha, have limitations in predicting long-term disease progression. Emerging biomarkers offer novel insights into systemic disease mechanisms and personalized medicine. Soluble urokinase plasminogen activator receptor has been identified as a stable and predictive marker of systemic inflammation, with strong associations with CKD, atherosclerosis, and coronary artery disease. Galectin-3 is a key regulator of fibrosis and inflammation across multiple organ systems, while Growth Differentiation Factor-15 has been implicated in mitochondrial dysfunction and cardiovascular aging. Furthermore, microRNAs such as miR-126 and miR-423-5p show promise as biomarkers for vascular integrity and heart failure progression, respectively. These biomarkers not only aid in early detection but also guide targeted interventions. Elevated levels of these markers support the use of sodium-glucose cotransporter 2 inhibitors for cardiorenal protection, and glucagon-like peptide-1 receptor agonists or dual glucose-dependent insulinotropic polypeptide and glucagon-like peptide 1 receptor agonists for metabolic and liver-related complications. Despite these advancements, the clinical integration of novel biomarkers remains limited. This review analyzes the pathophysiological mechanisms underlying CRHM syndrome and explores key biomarkers poised to enhance risk assessment and patient monitoring.